Determination of monosaccharides in Lycium barbarum fruit polysaccharide by an efficient UHPLC‐QTRAP‐MS/MS method. Issue 5 (21st January 2021) - Xu, Jun; Wang, Rui; Liu, Junlin; Cheng, He; Peng, Daiyin; Xing, Lihua; Shi, Suying; Yu, Nianjun
Abstract: Introduction: Pre‐column derivatisation using 1‐phenyl‐3‐methyl‐5‐pyrazolone (PMP) is a common method for monosaccharide determination. Herein, a specific ultra‐high‐performance liquid chromatography quadrupole trap tandem mass spectrometry (UHPLC‐QTRAP‐MS/MS) method was developed and used for the determination of monosaccharide composition of Lycium barbarum polysaccharide (LBP). Objective: Exploration of a new efficient method for monosaccharide determination. Methods: In our study, hydrochloric acid was used to hydrolyse the polysaccharide obtained from L. barbarum fruits. Principal component analysis (PCA) and technique for order of preference by similarity to ideal solution (TOPSIS) analysis were used for comprehensive evaluation of the samples. The results showed that LBP was composed of seven monosaccharides: galactose, arabinose, mannose, rhamnose, xylose, ribose, and glucose. The linear relationship of the seven monosaccharides was optimum within a certain concentration range. Quantitative recoveries of the seven monosaccharides from the samples ranged from 94.76% to 102.11%. Results: A rapid quantitative detection method was established, in which the hydrolysis time was reduced from 12 h to 2 h. By using LBP as one of the indexes to evaluate the quality of L. barbarum, L. barbarum from Zhongning County, Ningxia Province, was identified as having the best quality among the varieties tested. Conclusion: The UHPLC‐QTRAP‐MS/MS pre‐column derivatisation method used in this study was simple, accurate, and sensitive, with good repeatability, and can be used for quality evaluation and origin distinction of L. barbarum and other medicinal plants. Abstract : Achievement: A novel method for Lycium barbarum monosaccharide determination and basis for further exploration and evaluation of the internal quality and control of L. barbarum .